Comparison of set-up error for prostate cancer patients among three immobilization devices in Intensity modulated radiation therapy technique - Tongngarm , Wimonmart; Yabsantia, Sumalee (Journal of Thai Association of Radiation Oncology, 2021)
Background: Immobilization device is critical for providing the accuracy of prostate cancer treatment with intensity-modulated radiation therapy (IMRT) techniques. However, the positioning accuracy may depend on the type of immobilization devices. Objective: The objective of this study was to compare the set-up error of prostate cancer patients among 3 immobilization devices consisting of group 1 (Pillow+Knee), group 2 (Pillow+Pelvis Mask+Foot) and group 3 (Pillow+Vac Lock+Knee). Materials and methods: Twenty-five prostate cancer patients treated with the IMRT technique were enrolled in this study. The sample sizes were 5, 10, and 10 for immobilizations device group 1, group 2, and group 3, respectively. The treatment verifications were performed for each patient on the first three days followed by weekly by comparing electronic portal imaging device (EPID) and digitally reconstructed radiographs (DRRs) images, and data were retrospectively collected. In addition, set-up errors in the three immobilization groups were compared in the superior-inferior, left-right, and anterior-posterior directions. Results: The median set-up errors of 3 immobilization groups in left-right and anterior-posterior directions were less than 0.10 cm. There was no statistical difference among 3 groups of immobilization (p-value > 0.05). However, in the superior-inferior direction, a statistical difference (p-value < 0.001) was observed. The median set-up errors were -0.2±0.3, 0.1±0.4 and 0±0.2 cm for group 1, group 2 and group 3, respectively.Conclusion: The difference of set-up error among three immobilization devices was found only in the superior-inferior direction. Moreover, group 3 is the most reproducible immobilization, followed by group 2 and group 1, respectively.